Komunikasi Kepemimpinan Perempuan Suku Melayu Semende dalam Budaya Tunggu Tubang: Analisis Etnografi Komunikasi Model Speaking Dell Hymes - Dinata, Ehsan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study examines the leadership communication of Tunggu Tubang women in the customary culture of the Semende Malay Tribe in Pajarbulan Village, Semende Darat Ulu District, Muara Enim Regency. Tunggu Tubang places the eldest daughter as the heir and manager of family heirloom assets, as well as the leader in the customary kinship structure. This research aims to analyze the leadership communication practices of Tunggu Tubang women using an ethnography of communication approach with Dell Hymes' SPEAKING model, encompassing eight components: Setting and Scene, Participants, Ends, Act Sequences, Key, Instrumentalities, Norms, and Genre. This qualitative research employed in-depth interviews, participatory observation, and field documentation with nine purposively selected informants. Thematic analysis following Braun & Clarke (2013) was used. Findings reveal that Tunggu Tubang leadership is multidimensional and exercised through dialogic deliberation with customary elders, jurai, apit jurai, meraje, and expert advisors. Adaptive communication competence manifests in contextual code-switching between the Semende language in customary and religious domains, and Indonesian in village governmental coordination. Customary symbols such as the guci (trustworthiness), tebat/kolam (patience), jale (unity), kapak (justice), and tombak/kujur (honesty) function as communicative resources reinforcing leadership legitimacy. These findings affirm that Tunggu Tubang women's leadership constitutes an adaptive and relevant communicative leadership model, synergistically integrating family, social, symbolic, religious, and institutional dimensions in preserving social cohesion and cultural identity.